Analysis of the use of Extracorporeal Shock Wave Lithotripsy (ESWL) based on piezoelectric lithotripter for kidney stone - Dedy Setyawan (Indonesian Association of Physicists in Medicine (AIPM/AFISMI), 2021)
Extracorporeal shock wave lithotripsy (ESWL) is a non-surgical method that can be used to break stones in the urinary tract or kidney stones by focusing the shock wave from outside the body on the location of the stone. In its application, ESWL is classified as theranostics by applying the principles of medical physics in determining the location of kidney stones and biophysics in the therapeutic process. This study aimed to analyze the use of ESWL to treat kidney stones in Dr. Saiful Anwar Malang hospital. The ESWL machine analyzed was the ESWL PIEZOLITH 3000 Triple Focus, which used the Richard Wolf piezoelectric lithotripter, with serial number GA-A 175. This analysis was carried out by combining the results of the method of literature research, observation, and interview. Based on the results of the research, the therapy with the ESWL PIEZOLITH 3000 Triple Focus uses a shock wave generated by the piezoelectric effect of piezoelectric crystals that are arranged like a mosaic in a spherical cup and are then activated simultaneously by a pulse generator. During the observation from July 18, 2017 to July 27, 2017, the smallest dimension of the treated stone was 6 x 6 mm and the largest was 10 x 15 mm. The number of shock waves used is the same with an average of 4000. The power, frequency, and membrane pressure are adjusted with the patient's body condition. Various criteria and contraindications must be met to determine a candidate for a patient to gain satisfactory results. The therapy levels include the pre-therapy procedure, therapy implementation, and post-therapy. The success rate of therapy and the rate of retreatment are determined by the type of stone, the location of the stones, and the density of the stones.